2018
DOI: 10.1002/lno.11025
|View full text |Cite
|
Sign up to set email alerts
|

Physical dynamics structures and oxygen budget of summer hypoxia in the Pearl River Estuary

Abstract: A summertime hypoxia sporadically occurred in the lower Pearl River Estuary (PRE) for more than three decades. Although its mechanism has already been extensively studied, the topic on why seasonal hypoxia is persistent in patchy waters is still an open question. Here, we presented the investigation of physical dynamics structures and dissolved oxygen (DO) processes for controlling the spatial distribution and maintenance of coastal hypoxia. Field observations were conducted in the 2015 summer in the PRE and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 59 publications
(98 reference statements)
5
75
0
Order By: Relevance
“…Rabouille et al (2008) demonstrated that tidal mixing could disrupt stratification and break hypoxia. However, the DO concentration outside of the Lingdingyang sub-estuary exhibited a tidal fluctuation and spring-to-neap oscillation, with a maximum neighboring oxygen range only of 0.2 and 0.5 mg L -1 , respectively (Cui et al 2019). Our observations showed the maintenance of hypoxia during Leg 1 and the reinstatement of hypoxic or oxygen-deficient conditions from Leg 2 to Leg 3, both over the transformation from a neap tide to a spring tide (Fig.…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…Rabouille et al (2008) demonstrated that tidal mixing could disrupt stratification and break hypoxia. However, the DO concentration outside of the Lingdingyang sub-estuary exhibited a tidal fluctuation and spring-to-neap oscillation, with a maximum neighboring oxygen range only of 0.2 and 0.5 mg L -1 , respectively (Cui et al 2019). Our observations showed the maintenance of hypoxia during Leg 1 and the reinstatement of hypoxic or oxygen-deficient conditions from Leg 2 to Leg 3, both over the transformation from a neap tide to a spring tide (Fig.…”
mentioning
confidence: 55%
“…4a, b). It therefore acted as a barrier layer, with weak dissipation of oxygen into the bottom layer (Cui et al 2019). The inherent pycnocline between the offshore surface water and shelf benthic waters mainly driven by steep temperature gradients (Qu et al 2007), such as at Station A14, was observable as a second pycnocline in the plume region (e.g., stations A8 and F304, Fig.…”
Section: Physical Controls On the Maintenance Destruction And Reinstmentioning
confidence: 98%
See 2 more Smart Citations
“…Besides eutrophication (Diaz and Rosenberg, 2008), climate change (Altieri and Gedan, 2015) intensifies DO depletion. Estuaries and other regions of fresh water influence are typically very productive regions and often experience hypoxia (Conley et al, 2009;Cui et al, 2019;Obenour et al, 2013;Testa and Kemp, 2014). Natural and anthropogenic nutrient 50 load in these areas leads to intensive sedimentation of organic matter.…”
Section: Introduction 45mentioning
confidence: 99%